Importance of numerical analyses for determining support systems in tunneling: A comparative study from the trabzon-gumushane tunnel, Turkey - Kanik, Mustafa; Gurocak, Zulfu (Pergamon-Elsevier Science Ltd, 2018)
In this study, we determined the consistency of support elements from empirical rock mass classification systems, to obtain optimum support elements via comparative numerical analyses. For this purpose, the Macka tunnel, on the Trabzon-Gumushane highway and still under construction, was selected as the study area. Along the tunnel route, Late Cretaceous-aged Catak, Macka and Esiroglu Formations crop out. All the formations are cut by a Late Cretaceous Kackar Rhyodacite. Laboratory and field studies were done to determine the properties of the rock material and discontinuities. The results were used to define rock mass properties. Preliminary support systems were defined by using Rock Mass Rating (RMR), Rock Mass Quality (Q) and Rock Mass Index (RMi) systems, respectively. The suggested support elements of all classification systems were in turn evaluated using the Finite Elements Method (FEM), allowing the thickness of the plastic zone and total displacement values to be determined. Results of the analyses showed that it is possible to remove the instabilities around the tunnel section by applying lower numbers of support elements. When using the support systems from the numerical analyses it was found that the optimum support systems were compatible with the support systems suggested by the RMi system. Besides, when the shotcrete strength was increased to 40 MPa, the displacements and thickness of the plastic zone around the tunnel could be reduced to minimal values. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Empirical method; Finite element method; Numerical analyses; Support system; Tunneling